The relationship between perceived barriers to physical activity and leisure activity types in adolescence - Cihan Ayhan; Huseyin Gümüş; Bilal Çağlayan (ROL Spor Bilimleri Dergisi, 2023)
Despite the benefits of physical activity and exercise for human health, many people do not engage in physical activity and exercise despite the well-known benefits for human health. Without access to active commuting or other school-related physical activity opportunities, adolescents are at risk of increased screen time use and weight gain. Physical activity barriers need to be investigated especially in adolescence. This study investigates the relationships between specific types of leisure activities and barriers to physical activity in adolescence. The study was undertaken with 1312 students in 14 different schools in Ankara City. Hierarchical multiple regression analyses were conducted to examine the relationships between specific types of leisure activities (outdoor, physical, hobbies and indoor, cultural, home-centered, and social and volunteering) and outcome variables. After controlling for covariates, it was revealed that outdoor activities and social activities were associated with all outcome variables. Volunteer activities were positively related to health perception. Negative relationships were observed between safety barriers and physical activities, individual barriers, and cultural activities. These findings suggest that promoting positive social interaction in recreational settings and encouraging participation in volunteer activities are important factors contributing to physical activity during adolescence.